A Comparison of Playfulness Levels of the Secondary Students in Kayseri and Trabzon Cities - Hazar, Muhsin; Beyleroglu, Malik; Tingaz, Emre Ozan; Gokyurek, Belgin; Esenturk, Oguz Kaan (European Scientific Journal, ESJ, 2017)
The aim of the study is to draw a comparison of 11-14 age group secondary school students playfulness level to play games which consist of physical activity. It also aims to evaluate playfulness level in terms of various parameters. For this purpose, 11-14 age group students’ playfulness level were examined according to cities, gender, and ages. A total of 523 11- 14 year-old students, including 303 from Kayseri and 220 from Trabzon, and some various schools formed a study group for the research conducted in the relational model. “Playfulness scale for playing games that consist of physical activity of children of 10-14 age group” that was developed by Hazar (2014) was used in the data collection. Based on the research, the level of playfulness of the participants was found to be "good" at 3.40-4.19. Students living in Kayseri and Trabzon were found to have "good" in terms of social adaptation, wish to play game, wish to win, and in general. Students in Kayseri "good" level had a playfulness at "medium" level in Trabzon. Due to the comparison of male and female student scores, it was found that there was a significant difference in favor of male students in game play overall, game passion, and risk taking dimensions. Girls are more likely to have social adaptation, playfulness, and a meaningful difference generally. Also, girls who live in Kayseri are more likely to be students. They wish to play game, social adaptation, wish to win, and risk taking. Meaningful differences can however be seen based on the scores of the 11 and 12 year students.